Modified SSOR-like method for augmented systems - Wen, Chun; Huang, Ting-Zhu (Mathematical Modelling and Analysis, 2011)
For solving the augmented system, Golub, Wu and Yuan and Zheng, Wang and Wu have presented the SOR-like methods and SSOR-like methods, respectively. In this paper, the SSOR-like method with two real parameters ω and α is established for solving the augmented system, which is the extension of the SSOR iteration method, and the new method is called the modified SSOR-like method (MSSOR-like method). The convergence of the MSSOR-like method is studied, and the function equation relating the parameters and eigenvalues of the iteration matrix of this method is obtained. Numerical experiments show that the MSSOR-like method with proper preconditioning matrix and parameters is better than the SOR-like method and the SSOR-like method.